Circulating antibodies against leukotoxin A as marker of periodontitis Grades B and C and oral infection with Aggregatibacter actinomycetemcomitans. Issue 12 (17th April 2021) - Damgaard, Christian; Danielsen, Anne Katrine; Enevold, Christian; Reinholdt, Jesper; Holmstrup, Palle; Nielsen, Claus H.; Massarenti, Laura
Abstract: Background: The facultative bacterium Aggregatibacter actinomycetemcomitans (Aa) is strongly associated with periodontitis and is occasionally found in periodontally healthy subjects. We aimed to determine the prevalence of salivary Aa among patients with either periodontitis Grade B (periodontitis‐B) or Grade C (periodontitis‐C), periodontally healthy controls (HCs), and to determine if systemic antibodies against Aa or its virulence factor leukotoxin A (LtxA) may serve as biomarkers that reveal the oral presence of the bacterium and discriminate subjects with periodontitis‐C, periodontitis‐B, or no periodontitis from each other. Methods: Serum and unstimulated saliva samples were collected from patients with periodontitis‐C (n = 27), patients with periodontitis‐B (n = 34), and HCs (n = 28). Serum level of immunoglobulin G antibodies to fragmented whole Aa and to LtxA were quantified using a bead‐based assay. Aa was identified in saliva using quantitative polymerase chain reaction (qPCR). All analyses were adjusted for age, sex, and current smoking status. Results: Aa was present in saliva from 11% of HCs, in 32% of patients with periodontitis‐B ( P = 0.04 versus HCs), and in 37% of patients with periodontitis‐C ( P = 0.02 versus HCs). Serum antibodies to fragments of Aa associated significantly with periodontitis‐C ( P = 0.03), while serum anti‐LtxA antibodies associated with both periodontitis‐B and periodontitis‐C ( P = 0.002 and P = 9×10 −4, respectively). Moreover, a significant association between serum anti‐LtxA antibodies and Aa count in saliva was observed ( P = 0.001). On the basis of serum anti‐LtxA antibody levels, patients with periodontitis could be discriminated from HCs (AUC = 0.74 in ROC curve‐analysis, P = 0.0003), and carriers of Aa could be discriminated from non‐carriers (AUC = 0.78, P <0.0001). Conclusions: Aa is highly prevalent in saliva of patients with periodontitis‐B or periodontitis‐C. Systemic immunoglobulin G antibodies against LtxA distinguish patients with periodontitis, regardless of grade, from HCs, while their quantity reflects the concurrent bacterial burden in the oral cavity.